The levels of urine calcium and deoxypyridinoline in patients with metastatic bone disease treated with palliative radiotherapy - Topkan, Erkan; Özyi?it, Gökhan; Gülbaş, Hülya; Karao?lu, Aziz (My University, 2004)
We prospectively evaluated the predictability of urine calcium and deoxypyridinoline (DPD), the two bone resorption markers, in the assessment of objective response to palliative radiation therapy (RT) for metastatic bone disease. Nineteen patients with radiographic evidence of metastatic bone disease due to breast or lung primaries, and suffering from persisting pain despite analgesic treatment were enrolled in this prospective study. There were 7 female and 12 male with a median age of 58 years (range 43 to 84 years). Urine samples for the measurement of urinary calcium and DPD levels were taken at the beginning of RT, sixth week, and twelfth week following RT. All patients received a total dose of 30 Gy in 3 Gy daily fraction doses 5 days a week for 10 days. Mean urine calcium and DPD levels before RT for whole patients were 17.53 ± 3.60 g/dl/?mol creatinine, and 100.12 ± 70.39 pmol/?mol creatinine. Fourteen patients (Group I) were alive with no evidence of progression of metastatic bone disease. Urine calcium and DPD levels were found to show a significant and progressive decrease after RT in Group I patients (p<0.001 for urine calcium and p=p<0.001 for urine DPD). Clinical and radiological evaluation revealed further bone dissemination of malignancy in five patients (Group II). Urine DPD and calcium concentrations were found to increase significantly in Group II patients (p=0.006 for urine calcium and p=0.009 for urine DPD). Our preliminary results demonstrated that both urine calcium and DPD may serve as valuable objective tools for assessing response to palliative RT of metastatic bone disease, and may serve as early predictors of disease progression.
Kemik metastazli hastalarda palyatif radyoterapi sonrasi i?drar kalsiyum ve deoksipiridinolin seviyeleri
Keywords: Deoxypyridinoline; Metastatic bone disease; Palliative radiotherapy; Urine calcium